2014
DOI: 10.1016/j.crvi.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-treatments and temperature on seed viability and germination of Juniperus macrocarpa Sm.

Abstract: The effects of collecting season, collection site, laboratory pre-treatments and temperatures on seed viability and germination of Juniperus macrocarpa were investigated. Ripe cones were collected in four Sardinian dune systems, in two seasons, from plant and soil. Warm (W) and cold (C) stratifications, two combinations of them (W + C, C + W), and no pre-treatment (0) were applied. Seeds were incubated in a range of constant (10-25 8C) and an alternating (25/10 8C) temperature regime. Seed viability was low (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Coastal dunes are harsh environments for the establishment and survival of plant species because of intense wind, salt-spray, occasional inundation by seawater and sand movement (Ripley and Pammenter 2008;Cogoni et al 2013;Pinna et al 2014;Del Vecchio et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Coastal dunes are harsh environments for the establishment and survival of plant species because of intense wind, salt-spray, occasional inundation by seawater and sand movement (Ripley and Pammenter 2008;Cogoni et al 2013;Pinna et al 2014;Del Vecchio et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was found that very low J. polycarpos plant production was due to the decreased seed germination level [9]. In several Juniperus species, the main reason for this is the deep physiological dormancy of the seeds [41], which prevents their germination and is difficult to break. Attempts made by scientists to improve the germination efficiency of seeds of particular species using different techniques were not always successful.…”
Section: Seed Germinationmentioning
confidence: 99%
“…Seed germination is an important process in the plant life cycle and it is influenced by environmental and physiological dormancy factors [12]. O. grandiflora has shown that the breaking of dormancy in its seeds did not have special requirements; furthermore, these had 100% germination without the stimulus of exogenous plant growth regulators supplied (Fig.…”
Section: Plant Material Disinfection Of Follicles Germination and mentioning
confidence: 99%